Specialized terminology of the Polish Penal Code in German translations - Pietrzak, Agnieszka (Acta Universitatis Lodziensis. Folia Germanica, 2023)
The aim of this article is to present the results of an analysis of the terminology of the Polish Criminal Code and its equivalents taken from three translations of the code into German. Scientific corpus includes Polish Criminal Code and the following three translations: DE-IURE-PL (2019), C.H. Beck (2012) and Max-Planck-Institut (1998). The method used is comparative legal analysis. The results of the analysis may find application in academic teaching and be used in the development of courses in legal translation.